Professional knowledge & skills in the early years - Verity Campbell-Barr (Los Angeles, Calif. : Sage, 2019)
Providing international examples and theoretical discussions on the challenges and rewards of working in the early years, this book seeks to identify, recognise and celebrate those who work in early years education
Keywords: Administration; Education, Primary; Early childhood education